Assessing urban community parks from an age-friendly perspective: a multi-criteria decision-making approach - Dong, Weidan; Sun, Shuai; Fu, Yinghang (Frontiers in Public Health, 2025)
IntroductionWith the acceleration of population ageing, community parks have become vital spaces for older adults’ daily activities. The age-friendliness of their spatial environment directly impacts the well-being of the older adult population. Scientifically evaluating the age-friendliness of community parks and proposing optimization strategies is crucial to promoting the physical and mental well-being of the older adults and enhancing the quality of urban public services.MethodsThis study established an evaluation index system for the age-friendliness of community parks through field surveys, literature review, expert screening, and statistical validation. User perception data were collected via questionnaires, and a combination of the Analytic Hierarchy Process (AHP) and Entropy Weight Method was used to determine weights from both subjective and objective perspectives. Subsequently, the TOPSIS model was employed to conduct a comprehensive assessment of three typical community parks in Beijing.ResultsThe results indicate that path accessibility, ageing of leisure facilities, social space design, cultural, educational and recreational functions, and physical environment security are the most influential factors affecting the age-friendliness of community parks, with the highest weights. In contrast, intelligent service facilities, seasonal adaptability services, and community activities organization are relatively less prioritized by older adults. The findings reveal that the core needs of older adults in community park usage are centered on four key aspects: accessibility, recreation, social interaction, and safety. Furthermore, a comparative analysis revealed significant differences in overall age-friendliness across the three case parks, with Wanshou Park performing the best, Nanguan Park ranking second, and Shuangxiu Park ranking lowest.DiscussionBased on these findings, strategies to enhance the age-friendliness of community parks were proposed. This study provides both theoretical support and practical reference for the scientific assessment and optimization of community park age-friendliness, offering important insights for the adaptation of urban public spaces to an aging society.